The efficacy and safety of mecobalamin combined with Chinese medicine injections in the treatment of diabetic peripheral neuropathy: A systematic review and Bayesian network meta-analysis of randomized controlled trials - Ma, Yuqi; Chen, Ji; Huang, Xinggui; Liu, Yuan (Frontiers in Pharmacology, 2022)
Background: In recent years, people pay more and more attention to diabetic peripheral neuropathy (DPN). As a neurotrophic agent, mecobalamin is able to repaire nerves, which has already become a consensus among experts. However, it has been found that mecobalamin has poor effect to increase nerve conduction velocity, which is an important indicator. Clinical data have shown that Chinese medicine injection, combined with mecobalamin injection, can significantly improve nerve conduction velocity of the limbs. Nevertheless, several kinds of Chinese medicine injections have been used to treat DPN. The effect of these Chinese medicine injections for DPN are various. Therefore, it is necessary to evaluate the effectiveness of Chinese medicine injections combined with mecobalamin in the treatment of DPN. Methods: All relevant articles published before 12 March 2022 were searched in eight electronic databases. Randomized controlled trials (RCTs) on Chinese medicine injections plus Mecobalamin for DPN were identified according to inclusion criteria, and were assessed using the revised Cochrane risk of bias tool (ROB2.0). R software and stata15 was used to create the ranking probabilities and network meta-analysis. Results: A total of 80 RCTs involving 6,980 patients were included. The results showed that mecobalamin plus Dengzhanxixin injection (ME + DZXX) ranked first in overall response rate [RR = 1.64, 95% CI (1.26, 2.21)] and median motor nerve conduction velocity [MD = 9.46, 95% CI (5.67, 13.28)]. Then, mecobalamin plus Kudiezi Injection (ME + KDZ) had the best effect in median sensory nerve conduction velocity [MD = 10.41, 95% CI (−13.31, −7.52)], and mecobalamin plus Honghua injection (ME + HH) ranked highest in common peroneal motor nerve conduction velocity [MD = 6.8, 95% CI (4.13, 9.49)] and common peroneal sensory nerve conduction velocity [MD = −6.25, 95% CI (−8.85, −3.65)]. Conclusion: This study determined the efficacy of different Chinese medicine injections combined with mecobalamin. DZXX may be the best adjunctive Chinese medicine injection for DPN patients. However, due to potential risk of bias and limited RCTs, our results need to be treated with reservations.